Novel structured catalytic systems - cartridges on the base of fibrous catalysts; Chemical Reactors (CHEMREACTOR-22) - Zagoruiko A. N. Andrey Nikolaevich; Lopatin S.; Mikenin P.; Zazhigalov S.; Pisarev D.; Baranov D. (2016, 2016)
Title screen